Chronostratigraphy of KNM-ER 3733 and other Area 104 hominins from Koobi Fora. Issue 86 (September 2015) - Lepre, Christopher J.; Kent, Dennis V.
Abstract: A magnetostratigraphy for ∼60 m of Koobi Fora Formation sediment in Area 104 was derived from 46 oriented samples that produced well-resolved characteristic magnetizations from progressive thermal demagnetization. Approximately 59 m below the Morte Tuff, previously dated to ∼1.51 Ma (millions of years ago), the Olduvai-Matuyama boundary (∼1.78 Ma) was found to be at the level of marker bed A2—inconsistent with the Area 102 type section and thus contrary to fossil dating schemes that utilize temporal equivalence between A2 [104] and A2 [102]. The magnetostratigraphic data, coupled with the Morte Tuff, provide a means to interpolate new ages for marker beds A2 [104] and the White Tuff, as well as multiple Area 104 hominin fossils. Noteworthy is the new date of ∼1.63 Ma for KNM-ER 3733, which now implicates KNM-ER 2598 as the sole early African Homo erectus fossil demonstrably older than Dmanisi and Java Homo specimens. Re-dating KNM-ER 3733 creates a ∼300-kyr gap at 1.9 to 1.6 Ma in the African fossil record of H. erectus, which might be partially spanned by hand axes recently dated at ∼1.76 Ma, if the Acheulian is indeed proprietary to this species.